Client and contractor roles in schedule incentive/disincentive projects: An empirical study from India. Issue 3 (11th February 2019) - Hasan, Abid; Jha, Kumar Neeraj
Abstract : Purpose: Delays in construction projects can be very expensive due to their adverse effects on project cost and profit margin. To overcome this problem, clients in the construction industry sometimes use schedule incentive/disincentive (I/D) contracting strategy. However, previous studies have shown that inadequate understanding and wrong implementation of schedule I/D provisions could result in unintended results. Moreover, the use of the I/D contracting method is in its initial stages in many countries such as India. The purpose of this paper is to identify various factors that are essential for schedule I/D success in construction projects. Design/methodology/approach: A questionnaire survey was conducted among experienced professionals (clients, contractors and consultants) from across the Indian construction industry. Findings: Top success factors related to clients in the descending order of their importance are: realistic targets; detailed guidelines for I/D implementation; close coordination with other stakeholders; correct estimation of I/D duration and amount; and imposing disincentives after due consideration. Meanwhile, factors related to contractor organisations are: continuous monitoring and control; thorough understanding of schedule I/D targets; specific considerations in appointing senior project personnel; effective communication; and proper labour management. Research limitations/implications: This empirical research was conducted in the Indian construction industry. Similar studies from developed construction markets may provide more insights into the successful use of schedule I/D provisions in construction projects. Practical implications: The uptake of these recommendations is likely to increase the success of schedule I/D provisions in construction projects, especially in developing countries where the use of I/D contracting strategy is not very popular. Originality/value: This research highlights the specific roles of both clients and contractors in the success of schedule I/D projects in developing countries such as India.